Sociology-based character education strategies and their role in shaping moral development in boarding-based islamic education - Nurdiansyah, Muhammad Hafidza Daffa; Novikasari, Ifada (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Character education is a foundational aspect of Islamic education, particularly at the primary level, where students begin to internalize moral and social values. In Indonesia, boarding-based madrasah institutions offer a unique environment for character formation due to their immersive and socially intensive settings. This study aims to explore the extent to which character-building strategies based on the sociology of education contribute to the character development of sixth-grade students at MIN 1 Banyumas, a state Islamic elementary school with a residential program. The theoretical framework draws from sociological theories emphasizing the role of structured social environments in shaping individual behavior and identity. The strategies examined in this study include daily habituation practices, exemplary modeling by educators and caregivers, value-based communication, and intentional peer interaction designed to reinforce shared norms and ethics. Methods: This research employs a quantitative associative design involving total sampling of all students living in the school’s dormitory. Data were collected using a Likert-scale questionnaire that had undergone tests for validity and reliability. The data were then analyzed using simple linear regression to determine the relationship between character-building strategies and character outcomes. Findings: The results reveal a statistically significant influence, with a p-value of 0.045 and an R-squared value of 0.136. These findings suggest that 13.6 percent of the variance in character development can be attributed to the implemented strategies. Conclusion: The study concludes that character formation in Islamic boarding environments benefits significantly from structured, socially embedded educational strategies. Novelty/Originality of this article: It calls for the institutionalization of sociologically grounded approaches to character education that are sensitive to students’ daily interactions, cultural context, and moral experiences.